2018
DOI: 10.1002/prep.201800041
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and Combustion Characterization of Ca(IO3)2‐based Pyrotechnic Composites with B, Al, and Ti

Abstract: This paper studies the reactive behavior of calcium iodate with Al, B and Ti fuel particles as a thermal and iodine release source for neutralization of biological materials that might be employed in weapons. Two different calcium iodate particle length scales (micron and submicron) with different fuel/oxidizer ratios were used to prepare the iodized nanopyrolants. The optimal ratio was found to be the one with equivalence ratio of 2.0 for all the three fuels. The reactivity of the pyrolants can be enhanced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Figure b shows the snapshots of the thermite reaction recorded using a high-speed camera for 7.5 wt % Si/Al/Ca­(IO 3 ) 2 mesoparticles ignited by rapid heating on a Pt wire (heating rate ∼ 10 5 K/s). The mesoparticle composites show a violent reaction with an ignition temperature of ∼870 K. Previous studies have shown that metal iodate decomposition occurs prior to the thermite reaction, implying that combustion is limited by fuel release rather than by the oxidizer availability. , In order to probe the ignition mechanism and reaction products, the mesoparticle powders were coated on a Pt wire, followed by rapid, resistive heating to yield the ignition temperature and mass spectra of products from the thermite reaction. Figure b shows time-resolved mass spectra from the thermite reaction of a typical Al/Si/Ca­(IO 3 ) 2 mesoparticle composite under vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…Figure b shows the snapshots of the thermite reaction recorded using a high-speed camera for 7.5 wt % Si/Al/Ca­(IO 3 ) 2 mesoparticles ignited by rapid heating on a Pt wire (heating rate ∼ 10 5 K/s). The mesoparticle composites show a violent reaction with an ignition temperature of ∼870 K. Previous studies have shown that metal iodate decomposition occurs prior to the thermite reaction, implying that combustion is limited by fuel release rather than by the oxidizer availability. , In order to probe the ignition mechanism and reaction products, the mesoparticle powders were coated on a Pt wire, followed by rapid, resistive heating to yield the ignition temperature and mass spectra of products from the thermite reaction. Figure b shows time-resolved mass spectra from the thermite reaction of a typical Al/Si/Ca­(IO 3 ) 2 mesoparticle composite under vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…In another study [112], the performances of Al and B were compared with those obtained using Ti in place of them. The ignition temperatures of Ti/Ca(IO 3 ) 2 thermites were considerably lower than Al/Ca(IO 3 ) 2 or B/Ca(IO 3 ) 2 ones and it was speculated that this difference was ascribable to the melting point of Al and to the diffusive resistance to interphase contact due to molten B 2 O 3 on B surface.…”
Section: Biocidal Thermites With Salts Of Iodine Oxyacidsmentioning
confidence: 99%